(untitled) (Studia austriaca, 2012)
Elfriede Jelinek’s dramas focus on the power of mental images. Her “language surfaces” describe spaces of ideas which are created by associations und amalgams. These are hybrid intellectual places, where those who were driven out from history try to come back. This theatrical aesthetics evolves thanks to circumlocutions around a symbolic und concrete «lieu de mémoire» (Pierre Nora): Auschwitz. Elfriede Jelinek uses the ancient “method of loci” to question the link between theatre and “lieu de mémoire”, while building up intellectual places very similar to contemporary memorials.